Open Reduction and Internal Fixation for the Treatment of Symptomatic Osteochondritis Dissecans of the Femoral Head in Patients With Sequelae of Legg-Calvé-Perthes Disease. Issue 3 (March 2020) - Lamplot, Joseph D.; Schoenecker, Perry L.; Pascual-Garrido, Cecilia; Nepple, Jeffery J.; Clohisy, John C.
Abstract : Background: Osteochondritis dissecans (OCD) is estimated to occur in 2% to 7% of patients with Legg-Calvé-Perthes disease (LCPD). Unstable osteochondral fragments secondary to LCPD may produce mechanical symptoms requiring surgical intervention. Reattachment of the fragment with open reduction and internal fixation (ORIF) may provide good clinical outcomes. The purpose of this study is to report short-term clinical and radiographic results of ORIF for the treatment of symptomatic osteochondral lesions resulting from LCPD. Methods: Clinical data including patient demographics and patient-reported outcome scores were collected prospectively. All patients underwent preoperative radiographs and magnetic resonance imaging confirming an unstable OCD fragment as well as postoperative radiographs at regular intervals. Indications for ORIF of the OCD fragment were hip pain and mechanical symptoms with radiographic evidence of LCPD and a magnetic resonance imaging demonstrating an OCD fragment of the femoral head. Osteochondral fragment instability was confirmed intraoperatively. Preoperative and postoperative physical examination findings were documented. All patients failed a course of nonsurgical treatment (activity modification, anti-inflammatories, and physical therapy). Results: From a total of 64 consecutive patients treated with hip preservation surgery for LCPD, 7 patients with symptomatic OCD secondary to LCPD were treated with surgical hip dislocation and ORIF of the femoral head osteochondral fragment. OCD size lesion ranged from 200 to 625 mm 2 . All patients reported marked clinical improvement, with resolution of both pain and mechanical symptoms. Radiographs at final follow-up demonstrated complete osteochondral fragment healing without implant failure. Mean follow-up was 4.6 years (range, 1.1 to 7.4 y). There was a significant postoperative improvement in measured internal rotation in flexion (5.0±5.0 to 16.4±9.8; P =0.02). Modified Harris Hip Score markedly improved from baseline to final follow-up (47.8 to 82.7; [INCREMENT]34.9; minimal clinically important difference, 11; P =0.002), with all patients meeting minimal clinically important difference for modified Harris Hip Score. There were no complications and no progression of osteoarthritis in all patients at final follow-up. Conclusions: We have demonstrated both predictable radiographic healing and marked clinical improvement following ORIF of symptomatic post-Perthes OCD lesions. We advocate ORIF for symptomatic osteochondral lesions as a first-line surgical treatment for these patients due to the advantages of native osteochondral tissue preservation, predictable healing, and marked clinical improvement. Level of Evidence: Level IV—case series. Abstract : Supplemental Digital Content is available in the text.